Different Versions of the Easterlin Paradox: New Evidence for European Countries - Caspar F. Kaiser; Maarten C.M. Vendrik (Institute of Labor Economics (IZA), 2018)
Richer people are happier than poorer people, but when a country becomes richer over time, its people do not become happier. This seemingly contradictory pair of findings of Richard Easterlin has be-come famous as the Easterlin Paradox. However, it was met with counterevidence. To shed more light on this controversy, we distinguish between five different versions of the paradox. These versions apply to either groups of countries or individual countries, and to either the long or the medium term. We argue that the long term is most appropriate for testing the paradox, and that tests of the paradox should always control for an autonomous time trend. Unfortunately, this requirement renders the long-term version of the paradox for individual countries untestable. We test all other versions of the paradox with Eurobarometer data from 27 European countries. We do so by estimating country-panel equations for mean life satisfaction that include trend and cyclical components of per capita GDP as regressors. When testing variants of the paradox that apply to groups of countries, we find a clear and robust confirmation of the long- and medium-term versions of the paradox for a group of nine Western and Northern European countries. Moreover, we obtain a non-robust rejection of the medium-term variant of the paradox for a set of eleven Eastern European countries. On the level of individual countries, the medium-term variant of the paradox clearly holds for the nine Western and Northern European countries, but is consistently rejected for Greece, Ireland, Italy, and Spain. In the case of the Eastern European countries, the medium-term version of the paradox is rejected for Bulgaria, Lithuania, and Poland. As the Western and Northern European countries have a high per capita GDP as compared to that of Southern and Eastern European countries, our results are in line with the finding of Proto and Rustichini (2013), who find a non-monotonic relation between per capita GDP and life satisfaction over time which is positive for poorer countries, but flat (or negative) for richer countries.
Keywords: I31; I32; O11; 330; Hodrick-Prescott filter; economic growth; life satisfaction; happiness; Easterlin Paradox; European country panel